Factors Causing Credit Risks in Commercial Banks and Their Assessment - Shakhzod Abduvakhobov (Journal of Intellectual Property and Human Rights, 2023)
The article describes the nature of credit risks in commercial banks, the factors that cause them, and ways to assess risk factors. As a result of the research, recommendations on credit risk assessment were developed.